Tingkat Kepuasan Petani Terhadap Penggunaan Pupuk Hayati Boc-Srf dan Pupuk Hayati X dalam Meningkatkan Produksi Cabai Merah - Anggarawati, Sari; Sunengsih, Sunengsih; Wibaningwati, Dyah Budibruri; Suwarnata, Anak Agung Eka (Universitas Galuh, 2024)
Red chilli is a plant that has always been the subject of discussion because it can cause inflation in Indonesia. Even though demand is high, the lack of goods causes prices to soar. One effort to increase red chilli productivity is the use of fertilizer. The Center for the Study and Application of Technology (BPPT) has produced superior biological fertilizers, namely BOC-SRF Biological Fertilizers, which farmers use on red chilli plants. Farmers as consumers certainly feel satisfied or not after using this fertilizer or other biological fertilizers; therefore, it is necessary to research the level of satisfaction of farmers regarding the use of BOC-SRF Biofertilizer and Biological Fertilizer Hayati BOC-SRF with Hayati X in Sukatani Village, Pacet District, Cianjur Regency with 40 farmers as respondents. The analysis method uses the Customers Satisfaction Index (CSI), Important Performance Analysis (IPA) and Diagonal Analysis (Suharjo Split). As a result, farmers were very satisfied with the performance of BOC-SRF biofertilizer (CSI: 81%), while farmers using X biofertilizer were satisfied with an index value of 74.4%. The attribute that is the main priority but performs poorly when using BOC-SRF biological fertilizer is the